FABRICATION, OPTICAL PROPERTIES AND APPLICATIONS OF UNDOPED CHEMICAL BATH DEPOSITED ZnO THIN FILMS - Ezema, F. I. (Journal of Research (Science), 2025)
Thin films of ZnO were deposited on glass slides from aqueous solutions of zinc sulphate in which ammonium solution and TEA were employed as complexing agents. The film was studied for its optical properties using measurement from a Unico UV-2102 PC spectrophotometer, at normal incidence of light in the wavelength range of 200-1000nm and Olympus PMG for the photomicrograph. The optical characterization shows that the band gap of the deposited film vary with the annealing of the film; the band gap ranged between 1.60eV and 1.80eV. The films were found to have an average transmittance of greater than 55% in the VIS-NIR regions but become more transparent (above 70%) after annealing to 450K in an oven. The films exhibited average reflectance of greater than 11% in the same regions. Other optical parameters such as refractive index, extinction coefficient, real and imaginary dielectric constants and optical conductivities were also estimated. The film could find potential applications in the areas of antireflection thermal coatings for cold climates and for solar cell fabrication.